2020
DOI: 10.1002/pon.5379
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral prophylactic mastectomy for unilateral breast cancer in women at average risk: Systematic review of patient reported outcomes

Abstract: Objective The rate of contralateral prophylactic mastectomy (CPM) in women with early, unilateral cancer is relatively high and is increasing around the world a previous study. Women choose this option for many reasons other than reducing their risk of future cancer, including symmetry, reasons related to breast reconstruction and attempting to manage fear of recurrence. This systematic review evaluated patient‐reported quality of life outcomes following CPM. Methods A literature search of MEDLINE, PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(208 reference statements)
0
11
0
Order By: Relevance
“…Conversely, other studies have shown that breast-related quality of life remained high among both CPM patients and those who did not undergo CPM. 34 These mixed results suggest that treatment decision making remains a very patient-centered and patient-specific outcome.…”
Section: Costs and Benefits Of Peace Of Mindmentioning
confidence: 99%
“…Conversely, other studies have shown that breast-related quality of life remained high among both CPM patients and those who did not undergo CPM. 34 These mixed results suggest that treatment decision making remains a very patient-centered and patient-specific outcome.…”
Section: Costs and Benefits Of Peace Of Mindmentioning
confidence: 99%
“…“Outcome regret” occurs when a suboptimal, unfavorable, or an unanticipated outcome arises from the decision. The most prevalent outcome antecedents precipitating outcome regret include cancer recurrence, 9,33 dissatisfaction toward expected outcomes, 7,9,11,21,34,35,37,38 surgical complications, 35,37,38 a negative body image, 21,33,35 or the occurrence of lower sexual well‐being 11,21,35,38 …”
Section: Resultsmentioning
confidence: 99%
“…Even with the best intentions, clinicians can fall short in ensuring each step of the decision‐making process is adequate for informed decision‐making. “Process regret” is associated with decisions made in relation to the decision‐making process and can be attributed to (a) decisions made during time constraints due to the urgency of breast cancer treatment, 10,26,34,40 (b) poor communication or inadequate information on options, risks, and expected outcomes, 7,20,21,26,31,33,35,37,38,40–42 and (c) malalignment between the decision made and the patient's decision preference 26,37,41,43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they did not specifically address the issue of regret about treatment decisions, and were not able to generalise to the whole population because these reviews only included older women22 and women who had a mastectomy 23. Previous reviews on decision regret related to breast reconstruction24 and risk-reducing treatment25 26 also could not provide a holistic understanding of decision regret regarding EBC treatments because other treatments, such as BCS, chemotherapy and radiotherapy, are also common choices for EBC. To date, there is a lack of literature synthesis regarding levels of decision regret, what patients regret, and factors associated with decision regret regarding breast cancer treatments among women with EBC.…”
Section: Introductionmentioning
confidence: 99%